Study of Oribatids population on three types of land use at PT Nusantara VIII Plantation, Cisarua Sub-district, Bogor, West Java - Deseriana Bria; Rahayu Widyastuti; Sugeng Santoso (Journal of Degraded and Mining Lands Management, 2019)
Most of the forest area of PT Perkebunan Nusantara VIII have been converted to the plantation (tea, cacao, coffee) and agriculture, such as crops (intercropping of oranges and pineapple) areas. The forest conversion will affect soil biodiversity, which will reduce soil mesofauna population, such as the Oribatids group. Oribatids is one of the soil mesofauna which has a very important role in the soil as a decomposer. Because of its important role and their huge numbers in the soil, Oribatids can be used as a bioindicator of soil fertility. This study aimed to elucidate the abundance and diversity of Oribatids and the relationship between soil properties and population of Oribatids in three types of land use at PT Perkebunan Nusantara VIII. Soil and litter samples were taken in three different types of land use (tea gardens, intercropping, and secondary forests) using a simple random sampling method with a distance of each of the 15 sampling points of 100 m at a soil depth of 0-5 cm. Soil and litter samples were extracted using Berlese Funnel Heat Extractor. Oribatids identification was carried out until the family level, and the Oribatids diversity index were determined according to Shannon's diversity index. The identification results obtained in the three types of land use amounted to 24 families from 172 families found previously. The highest abundance of Oribatids was found in secondary forests both in the soil and litter layer (169.85 and 428.87 individuals/m², respectively), the lowest abundance of Oribatids was found in intercropping both in the soil and litter layer (89.17 and 229.30 individuals/m², respectively). According to Shannon Wiener (H'), the diversity index value ranges from 1.48-1.85 or it was categorized as a low-medium diversity value. The results of this study indicated that there was a positive correlation coefficient value from several families of Oribatids with soil pH, organic C, total N, C/N ratio, water content, and soil temperature.